Open urban spaces quality: A study in a historical square in Bath - UK - De Castro Fontes, Maria Solange Gurgel [UNESP]; Aljawabra, Faisal; Nikolopoulou, Marialena (My University, 2008)
The quality of open urban spaces is very important for urban vitality. Nowadays urban designers have to face the great challenge of designing urban spaces able to respond to people's need for liveable spaces. The success of these spaces depends on various aspects and the microclimatic condition has been recognized as one of the most influential. However, studies on thermal comfort in open space have shown that the user's thermal sensation does not depend only on microclimate parameters but also on other local qualitative aspects. Thus, environmental quality evaluation of successful public spaces can contribute to understand this issue. This paper focuses on a case study regarding Queen Square's environmental quality, a public space of historical importance in Bath-UK. The first stage of the research, a study on local characteristics and people observations, allowed a preliminary evaluation of the space performance, their social aspects, while it characterized and quantified the hourly variation of the space use in different days and seasons. In the second stage, short microclimatic surveys were carried out simultaneously with a perception survey through a questionnaire. The results show the strong vitality of the square and socioenvironmental significance, not only for its location in the urban context, but also for its historical value. The environmental quality of the square contributes to the users' sensation of comfort even in adverse climatic conditions. This research is part of a project that aims to investigate the impact of the environmental stimuli in the use of open spaces and intend to develop design strategies that aim to maximise the use of open spaces in different weather conditions.
Keywords: Open spaces; Outdoor thermal comfort; Quality of urban spaces